Belajar Eksperiensial Untuk Meningkatkan Pemahaman Generasi Muda Tentang Credit Union - Bartolomeus Yofana Adiwena; Eugenius Tintus Reinaldi; Lucia Trisni Widhianingtanti (JIP (Jurnal Intervensi Psikologi), 2022)
There are still many young people who do not know Credit Union (CU) well, so they are reluctant to become CU members. This program aims to make the younger generation know CU more deeply so that the desire arises to join CU and plan their future well. This program uses an experiential learning approach in the form of a digital infographic competition. The result showed that the experiential learning method used in this program has a positive effect on participants' knowledge and attitude about CU. In addition, this program was also quite successful in attracting the interest and attention of Instagram social media users, as indicated by a large number of likes on the contestants' social media.